2023
DOI: 10.1037/ppm0000369
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and correlates of celebrity culture hate.

Abstract: People tend to love and hate celebrities. The emotion of hatred can occur at the interpersonal level (i.e., directed at one celebrity) or the intergroup level (hatred toward celebrity culture in general). We sought to investigate hatred toward celebrity culture in general. We developed and evaluated the psychometric properties of the Celebrity Culture Triangular Hate Scale in a cross-cultural sample (Iranian and American). In addition to examining the effects of age and gender on hatred for celebrity culture, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…The US sample perceived higher support from celebrities in comparison to the Iranian sample. These findings concur with previous research (Shabahang, Aruguete, et al, 2021) showing greater hatred of celebrities in Iran compared to the US, indicating increased separation of the celebrity class from the community in Iran. This difference may be related to a history of Iranian government policies that resulted in blacklisting and banning celebrities because they were interpreted as symbols of modernity and Western influence that were incompatible with traditional Islamic values (Gholipour, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The US sample perceived higher support from celebrities in comparison to the Iranian sample. These findings concur with previous research (Shabahang, Aruguete, et al, 2021) showing greater hatred of celebrities in Iran compared to the US, indicating increased separation of the celebrity class from the community in Iran. This difference may be related to a history of Iranian government policies that resulted in blacklisting and banning celebrities because they were interpreted as symbols of modernity and Western influence that were incompatible with traditional Islamic values (Gholipour, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Higher scores indicate higher celebrity culture hatred. Shabahang, Aruguete, et al (2021) showed a three‐dimensional structure with robust model fit indices, inter‐item correlation (Persian version, r = from 0.54 to 0.92; English version, r = from 0.44 to 0.86), corrected item‐total correlation (Persian version, r = from 0.74 to 0.92; English version, r = from 0.68 to 0.90), and Cronbach's alpha (Persian version, Negation of Intimacy subscale's α = 0.93, Passion subscale's α = 0.97, and Commitment subscale's α = 0.97; English version, Negation of Intimacy subscale's α = 0.94, Passion subscale's α = 0.96, and Commitment subscale's α = 0.97).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations